Pemakaian undang-undang kecuaian dalam pengurusan ekologi dan habitat manusia di Melaka, Malaysia - Muhammad Rizal Razman; Mazalisah Matsah; Jamaluddin Md. Jahi; Kadir Arifin; Kadaruddin Aiyub; Azahan Awang (Environmental Management Society, Malaysia, 2009)
The law of negligence plays an important role in environmental management towards human habitat and ecology in order to tackle the problem of environmental pollution that occurs nowadays. The law of negligence is used to protect an individual that is suffering from injury, damage and loses due to the pollution of environment caused by other individual. Every individual that faces this problem will make a reasonable claim in court using with the proof of important element under the law of negligence that is a duty of care owed to the claimant by the defendant; a breach of this duty; damages resulting from this breach of duty; and reasonably proximate connection between the breach and the injury. Thus the uses of this law of negligence are one of the mechanisms for solving the problem of environmental pollution that is becoming serious to the human habitat and ecology surroundings. Therefore, this paper will reveal the suitability and relevancy of the use law of negligence to solve the problem of environmental pollution in Malacca